Pleadings, Minutes of Public Sittings and Documents - Intl. Tribunal for the Law of the Sea, Intl. Tribunal for the Law of the (Pleadings, Minutes of Public Sittings and Documents / Mémoires, Procès-Verbaux des Audiences Publiques et Documents Ser., 2017)
This volume contains the texts of written pleadings, minutes of public sittings and other documents from the proceedings in the Delimitation of the maritime boundary in the Atlantic Ocean (Ghana/Côte d'Ivoire), Provisional Measures . The documents are reproduced in their original language. The Special Chamber delivered its Order on 25 April 2015. It is published in the ITLOS Reports 2015 . Le présent volume reproduit les pièces de la procédure écrite, les procès-verbaux des audiences publiques et d'autres documents relatifs à la procédure concernant la Délimitation de la frontière maritime dans l'océan Atlantique (Ghana/Côte d'Ivoire), mesures conservatoires . Les documents sont publiés dans la langue originale utilisée. La Chambre spéciale a rendu son ordonnance le 25 avril 2015. L'ordonnance est publiée dans le TIDM Recueil 2015 .